Transverse relaxivity of iron oxide nanocrystals clustered in nanoemulsions: Experiment and theory. Issue 3 (18th September 2014) - Hak, Sjoerd; Goa, Pål Erik; Stenmark, Sebastian; Bjerkholt, Frøydis F.; Haraldseth, Olav
<x xml:space="preserve">Abstract</x> Purpose To compare experimental transverse relaxivities of iron oxide nanocrystals (IONC) as a function of clustering and magnetic field strength with different theoretical model predictions. Theory and Methods Well‐defined IONC clusters in nanoemulsions (NEs) of which both size and IONC loading could be judiciously tuned were developed. Transverse relaxivities were measured as a function of NE size and IONC loading at 20 and 300 MHz and compared with four theoretical model predictions. Polydispersity of the NEs was measured and taken into account in the theoretical calculations. Results Experimentally observed relaxivities were in between theoretical predictions from the fast diffusion regime and the static dephasing regimen. NE polydispersity significantly affected the theoretical T2 relaxivity. The effect of both the number of IONCs inside each droplet as well as the radius of the droplet itself was correctly described by a fast diffusion loose aggregate model, while the effect of increased magnetic field was in agreement with a static dephasing model. Conclusion The results suggest that both fast diffusion, originating from bulk water, and static dephasing phenomena, perhaps originating from water associated with the NE, play a role in transverse relaxivities of IONC aggregates. The developed aggregate system represents a powerful tool to further study these phenomena. Magn Reson Med 74:858–867, 2015. © 2014 Wiley Periodicals, Inc.